Carbene-catalyzed [4 + 2] cycloadditions of vinyl enolate and (in situ generated) imines for enantioselective synthesis of quaternary α-amino phosphonates - Sun, Jun (2020)
A carbene-catalyzed enantioselective addition of enals to five-membered cyclic imines is developed. The reaction gives chiral quaternary α-amino phosphonates bearing tetrasubstituted carbon centers with excellent enantioselectivities. The imine substrates can be generated in situ from the corresponding amines under an oxidative condition that is compatible with the carbene catalysis. Thus, a one-pot cross-dehydrogenative-coupling (CDC) reaction between enals and amines is also realized with high enantioselectivity remaining. The method provides quick enantioselective access to amino phosphonates with potential applications in medicines and pesticides.